2004
DOI: 10.1039/b409149c
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygenase-catalysed oxidation of alkylaryl sulfides: sulfoxidation versus cis-dihydrodiol formation

Abstract: Toluene- and naphthalene-dioxygenase-catalysed sulfoxidation of nine disubstituted methylphenyl sulfides, using whole cells of Pseudomonas putida, consistently gave the corresponding enantioenriched sulfoxides. Using the P. putida UV4 mutant strain, and these substrates, differing proportions of the corresponding cis-dihydrodiol sulfides were also isolated. Evidence was found for the concomitant dioxygenase-catalysed cis-dihydroxylation and sulfoxidation of methyl para-tolyl sulfide. A simultaneous stereoselec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…These include stereochemical correlation, [15] X-ray crystallography, [30,31] and 1 H NMR analysis of di-MTPA esters [31,32] or chiral boronates. [16,33] Unfortunately the chromatographic methods (CSPHPLC and CSPGC) did not give information on the absolute configuration and the NMR methods (di-MTPA esters and chiral boronates), and early CD studies [34] provided only tentative assignments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include stereochemical correlation, [15] X-ray crystallography, [30,31] and 1 H NMR analysis of di-MTPA esters [31,32] or chiral boronates. [16,33] Unfortunately the chromatographic methods (CSPHPLC and CSPGC) did not give information on the absolute configuration and the NMR methods (di-MTPA esters and chiral boronates), and early CD studies [34] provided only tentative assignments.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest literature method used for the direct determination of enantiopurity of benzene cis-dihydrodiols is chiral stationary phase HPLC (CSPHPLC) at ambient temperature. [13,16] Chiral stationary phase GC (CSPGC) has also been used but this required the formation of n-butyl boronate derivatives and elevated temperatures. [28,29] Comparison of optical rotations, and in some cases X-ray crystallographic analysis, [30,31] of cis-dihydrodiols and derivatives, has also been used to confirm their enantiopurity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes that make up the aromatic catabolic pathways are useful for bioremediation of environmental aromatic pollutants (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and for chemical synthesis (3,(12)(13)(14)(15). Studies of the aromatic pathways operative in common bacteria such as Escherichia coli and Pseudomonas putida (16,17) have provided a framework against which novel pathways of environmental bacteria can be understood (18,19).…”
mentioning
confidence: 99%
“…These later studies demonstrated that sulfoxidation reactions are common steps during oxidation of various sulfides. Different classes of enzymes are involved in these processes (2, 9, 37), including those initially not related to the metabolism of OSCs (8,26,46). Concerning Mo-dependent enzymes, two members of DMSO reductase family are also able to catalyze the oxidation of OSCs.…”
Section: Degradation Of Ms Has Been Previously Investigated In Onlymentioning
confidence: 99%